Adventures of a cat-whiskered girl - Pinkwater, Daniel Manus, 1941-; Brown, Calef (Boston : Houghton Mifflin Harcourt, 2010)
Big Audrey, who has cat-like whiskers, and her telephathic friend Molly set out on a journey to find out why flying saucers are landing behind the old stone barn in Poughkeepsie, New York, and, more importantly, to determine whether another cat-whiskered girl really exists.
A Junior Library Guild selection
"Houghton Mifflin Books for Children."
Keywords: Extraterrestrial beings -- Fiction; Cats -- Fiction; Science fiction; Humorous stories; Extraterrestrial beings -- Juvenile fiction; Cats -- Juvenile fiction; Science fiction; Humorous stories